AGENCY CONFLICT DALAM PENCAPAIAN PROFITABILITAS DENGAN LEVERAGE SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN SEKTOR RESTORAN, HOTEL DAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015) - Raden Bagus Faizal Irany Sidharta (Master of Management, Mataram University, 2017)
Indonesian Government nowadays is focusing to develop the tourism sector area while some problems in companies in sectors of restaurant, hotel and touris, related to institutional ownership, managerial ownership, leverage, and the company profitability. This research then is aimed at analyzing the effect of institutional ownership and managerial ownership on the leverage, at analyzing the effect of institutional ownership and managerial ownership on the profitability, at analyzing the effect of leverage on the profitability, at analyzing the effect of institutional ownership on the profitability through leverage, at analyzing the effect of managerial ownership on the profitability through leverage. This research employed the path analysis. The research showed that institutional ownership have positive and significant effect on the leverage, the managerial ownership has negative and significant effect on leverage, institutional ownership have negative and significant effect on the profitability, managerial ownership has positive and significant effect on the profitability, leverage has negative and significant effect on the profitability, institutional ownership has negative and significant effect on the profitability through leverage, managerial ownership has positive dan significant effect on the profitability through leverage.Keywords : Institutional Ownership, Managerial Ownership, Leverage and Profitability